2021
DOI: 10.1111/jdv.17561
|View full text |Cite
|
Sign up to set email alerts
|

New onset of mainly guttate psoriasis after COVID‐19 vaccination: a case report

Abstract: Our case series is limited by the absence of a control group and the retrospective analysis that was conducted. Large-scale prospective studies and pharmacovigilance monitoring are warranted to clarify the risks of VZV reactivation for all available SARS-CoV-2 vaccines. It should be determined whether all SARS-CoV-2 share a similar risk for this adverse reaction and should some of them be relatively safer in this regard, consideration should be given when choosing a vaccine for individuals most at risk for VZV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 6 publications
0
51
0
Order By: Relevance
“…Two middle-aged women developed a rosacea-like eruption 4 to 5 days after Ad26.CoV2.S and BNT162b2 vaccination [57]. In some patients, COVID vaccination may induce a new onset of psoriatic disease, presenting as chronic plaque psoriasis [58,59], palmoplantar psoriasis [60], guttate psoriasis [61], generalized pustular psoriasis [62], and even pityriasis rubra pilaris [63].…”
Section: Other Dermatosesmentioning
confidence: 99%
“…Two middle-aged women developed a rosacea-like eruption 4 to 5 days after Ad26.CoV2.S and BNT162b2 vaccination [57]. In some patients, COVID vaccination may induce a new onset of psoriatic disease, presenting as chronic plaque psoriasis [58,59], palmoplantar psoriasis [60], guttate psoriasis [61], generalized pustular psoriasis [62], and even pityriasis rubra pilaris [63].…”
Section: Other Dermatosesmentioning
confidence: 99%
“…2,3 In the literature, there are only few cases reporting the worsening of psoriasis after COVID-19 vaccine. [7][8][9][10] In our opinion, systemic treatment may reduce the risk of psoriasis flares after COVID-19 vaccination by the protection against the inflammatory process, which can cause the worsening of the disease. Hence, patients undergoing topical treatment for psoriasis have a higher risk of psoriatic flares compared with patients treated with systemic drugs.…”
Section: Dear Editormentioning
confidence: 99%
“…Wide range of cutaneous side effects are being reported with different types of SARS-CoV-2 vaccines including early-onset or delayed-type local injection reactions, maculopapular rash, erythema multiforme, pernio and urticaria. [48] Exacerbation of chronic inflammatory skin disorders such as psoriasis has also been recently described [49][50][51][52][53].…”
Section: Covid-19 Vaccines and Exacerbation Of Psoriasismentioning
confidence: 99%
“…Lehhman et al reported a new-onset guttate psoriasis after the BNT162b2 mRNA vaccine in a 79-year-old female, whose rash started 10 days after the first dose and flared up after the second dose [50]. Onsun et al reported a case of generalized pustular psoriasis developed 4 days after the first dose of the inactivated SARS-CoV-2 vaccine in a 72-year old man who had plaque psoriasis treated only with topical treatments [51].…”
Section: Covid-19 Vaccines and Exacerbation Of Psoriasismentioning
confidence: 99%
See 1 more Smart Citation